2009
DOI: 10.1007/s12597-009-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

An efficient heuristic algorithm for the bottleneck traveling salesman problem

Abstract: This paper describes a new heuristic algorithm for the bottleneck traveling salesman problem (BTSP), which exploits the formulation of BTSP as a traveling salesman problem (TSP). Computational tests show that our algorithm is quite effective. It found optimal solutions for many problems from the standard traveling salesman problem library (TSPLIB) problems. We also consider BTSP with an additional constraint and show that our BTSP heuristic can be modified to obtain a heuristic to solve this problem. Relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
8
0
3
Order By: Relevance
“…We consider some of those instances to show the efficiency of our HGA against binary search threshold (BST) heuristic [Ramakrishnan et al 2009] and HSCS algorithm [Ahmed 2010b]. Table II shows the comparative study of different algorithms for those instances of sizes up to 318 only.…”
Section: Computational Experiencementioning
confidence: 99%
See 3 more Smart Citations
“…We consider some of those instances to show the efficiency of our HGA against binary search threshold (BST) heuristic [Ramakrishnan et al 2009] and HSCS algorithm [Ahmed 2010b]. Table II shows the comparative study of different algorithms for those instances of sizes up to 318 only.…”
Section: Computational Experiencementioning
confidence: 99%
“…A sequential constructive sampling algorithm was developed by Ahmed [2000] to obtain heuristically optimal solution to the problem, and showed that the algorithm was better than the genetic algorithm of Ahmed et al [1999]. A binary search threshold heuristic has been developed to find heuristic solution for the general BTSP instances [Ramakrishnan et al 2009]. Recently, Ahmed [2010b] developed a hybrid sequential constructive sampling algorithm to find heuristic solution for the general BTSP instances and found better performance of the algorithm against algorithm of Ramakrishnan et al [2009] for some TSPLIB instances.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This benchmark was used for the classic TSP and BTSP. It provides optimum values for the first problem, but for reference on the second problem the instances from (Ramakrishnan et al 2009;Larusic et al 2012;Ahmed 2010) were used. -UKP (inp, 2005)-this data set contains some knapsack instances with optimal values and the package also contains an instance generator.…”
Section: Data Setmentioning
confidence: 99%